2010
DOI: 10.1051/0004-6361/201015902
|View full text |Cite
|
Sign up to set email alerts
|

The large amplitude outburst of the young star HBC 722 in NGC 7000/IC 5070, a new FU Orionis candidate

Abstract: Context. The investigations of the photometric and spectral variability of PMS stars are essential to a better understanding of the early phases of stellar evolution. We are carrying out a photometric monitoring program of some fields of active star formation. One of our targets is the dark cloud region between the bright nebulae NGC 7000 and IC 5070. Aims. We report the discovery of a large amplitude outburst from the young star HBC 722 (LkHα 188 G4) located in the region of NGC 7000/IC 5070. On the basis of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 13 publications
(13 reference statements)
2
74
0
Order By: Relevance
“…In August 2010 the star LkHα 188 G4 = HBC 722 has increased in brightness by more than 4 magnitudes and appears to be a new FU Orionis star, as reported by Semkov et al (2010), Miller et al (2011) and Aspin et al (in prep.). The North America and Pelican nebula region, and the dark cloud that divides them, L935, in a DSS image.…”
Section: Introductionsupporting
confidence: 71%
“…In August 2010 the star LkHα 188 G4 = HBC 722 has increased in brightness by more than 4 magnitudes and appears to be a new FU Orionis star, as reported by Semkov et al (2010), Miller et al (2011) and Aspin et al (in prep.). The North America and Pelican nebula region, and the dark cloud that divides them, L935, in a DSS image.…”
Section: Introductionsupporting
confidence: 71%
“…Magnitudes were estimated using the A to O comparison sequence of fifteen stars in the field around V2493 Cyg calibrated in BVRI by Semkov et al (2010). The used comparison sequence worked perfectly, covering the range of variability of the program stars, except for the V521 Cyg, which was brighter than comparison sequence stars.…”
Section: Star Sample and Measurementsmentioning
confidence: 99%
“…Adding to this, observations of PMS stars are usually made difficult by their faintness in quiescence and by the disturbance from sometimes heavy dust extinction, either surrounding the star or diffuse through the star forming region. Therefore, the rare outbursts of PMS stars always attract considerable interest, especially when they are long lasting, as in the case of new FUor objects (from the name of the prototype of this class, FU Ori), with one of the most recent and spectacular cases being that of HBC 722 = V2493 Cyg (Semkov et al 2010;Miller et al 2011;Munari et al 2010;Leoni et al 2010;Kóspál et al 2011;Armond et al 2011;Green et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of the other young stellar objects with both documented outbursts and FU Orionis-like near-infrared spectra (Reipurth & Aspin 2010;Semkov et al 2010;Miller et al 2011;Reipurth et al 2012), most have luminosities of at least 100 L . V2493 Cyg is the only one with a post-outburst luminosity (12 L ; Miller et al 2011) similar to or lower than the 28 L found for V2775 Ori.…”
Section: Pinpointing the Breakdown Of Magnetospheric Accretionmentioning
confidence: 99%
“…Greene et al (2008) distinguish between sources in which an outburst was actually observed and those that merely have outburst-like spectra, pointing to the importance of time monitoring to unambiguously classify each putative outburster and determine the frequency of these events. Since the advent of large-scale optical and IR monitoring programs, several young stellar objects have been observed to undergo significant increases in luminosity; e.g., V733 Cep (Reipurth et al 2007), V2492 Cyg ), V2493 Cyg (Semkov et al 2010;Miller et al 2011), V2494 Cyg (Aspin et al 2009), V2495 Cyg (Movsessian et al 2006), V900 Mon (Reipurth et al 2012), and V1647 Ori (Reipurth & Aspin 2004; Abrahám et al 2004;Briceño et al 2004), allowing a more thorough understanding of the range of outburst types and their frequencies.…”
Section: Introductionmentioning
confidence: 99%